PENGARUH REPUTASI UNDERWRITER, SIZE DAN USIA PERUSAHAAN PADA PENENTUAN HARGA IPO - Umi Murtini (Fakultas Bisnis UKDW, 2015)
Underpricing is a phenomenon occurring when companies do IPOS. This research aims to test theinfluence of underwriter reputation, size and age of the company's response underpricing companiesdo IPOS in the period 2009 to 2014. Testing is done using multiple regression. The test resultsshowed that the company's underwriter reputation and size have negative influence towardsundepricing. Meanwhile the age of the company have no effect against underpricing.Keywords: underpricing, underwriter, size, age of the company